Implementation of Notary Code of Ethics in an Effort to Uphold the Position of Notary in Grobogan Regency - Dyantama, Giovanni Resha (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
A Notary is not free from sanctions if they violate the applicable laws and regulations. When a Notary in carrying out his duties and positions is proven to have committed a violation, the Notary can be subject to or sentenced to sanctions in the form of civil, administrative, and Notary code of ethics and even criminal sanctions. The purpose of this study is to determine and analyze the role of the notary code of ethics in an effort to uphold the position of notary in Grobogan Regency and to determine and analyze what obstacles and solutions are faced by notaries in implementing the notary code of ethics in Grobogan Regency. The type of research used is empirical law. The approach method used in this legal research is the Statute Approach. The type of data uses primary data obtained from literature studies. The data analysis method used in this study is descriptive analytical. The problems of this study were studied using Role Theory, Legal Certainty Theory, and Legal Effectiveness Theory. Based on the conclusion of the research results, the role of the notary code of ethics in an effort to uphold the position of notary in Grobogan Regency is that the role of the notary profession is very important in legal traffic, especially in the field of civil law, along with the development of the era that requires anyone including notaries to develop themselves by being creative and innovative by using existing technology. Government policy in terms of integrated service processes is something that needs to be fully supported by the notary profession, in order to create a simple, fast, easy and cheap business process. The obstacles and solutions faced by notaries in implementing the notary code of ethics in Grobogan Regency are in the process of resolving violations of the notary code of ethics in Grobogan Regency, namely the very large number of notaries, with a wide working area, lack of awareness of notaries to comply with the code of ethics, and the provisions obtained by notaries are not sufficient during education, and there is still overlapping of the provisions for supervising the code of ethics between the Honorary Council and the Notary Supervisory Board. Meanwhile, for the Supervisory Board, namely the unavailability of a representative secretariat, lack of budget funds to carry out optimal supervision and coaching, lack of government attention/concern, and weak morals/behavior of Notaries in implementing the UUJN and the Notary Code of Ethics.